The impact of changing practice on improved outcomes of paediatric renal transplantation in the United Kingdom: a 25 years review. (26th March 2019) - Mumford, Lisa; Maxwell, Heather; Ahmad, Niaz; Marks, Stephen D.; Tizard, Jane
Summary: This review reports the outcomes of paediatric renal transplantation in the United Kingdom over the last 25 years. UK Transplant Registry data on 3236 paediatric renal transplants performed between 1 January 1992 and 31 December 2016 were analysed. Significant improvements in human leucocyte antigen (HLA) matching have been achieved; 84% of recipients received 000 or favourable (0 DR and 0 or 1 B) mismatched kidneys in 2016 compared with 27% in 1992. The median waiting time has increased from 126 days in 1999 to 351 days in 2016. Tacrolimus replaced ciclosporin in most immunosuppressive regimens after 2002. Renal transplant outcome has improved significantly, mainly because of a reduction in early graft loss. One‐year donation after brain death renal allograft survival for those transplanted from 2012 to 2016 was 98%, compared with 72% for those transplanted from 1987 to 1991. Renal allograft survival for first kidney only transplants at 1, 5, 10, 20 and 25 years were 89%, 79%, 65%, 42% and 33% respectively. Superior survival with living donor was maintained throughout the study period with 25‐year graft survival at 33% compared with 31% from deceased donor ( P < 0.0001). Changes in immunosuppression regimens, improvements in HLA matching and a reduction of cold ischaemia time may in part explain the improvements in graft survival.